Effects of movement control order (MCO) to online businesses : a study on micro enterprises in Kelantan / Azilawati Abdullah @ Abd Aziz ...[et al.] - Nik Wan, Nik Zam; Hussin, Siti Nor Adawiah; Noor Zainan, Nurul Izzah; Ab Rahman, Nurul Hidayah (2021)
Year 2020 wrote its own history when people around the world were made to stay at home due to the spread of the pandemic coronavirus (COVID-19). Pandemic COVID-19, which originated from Wuhan, China has caused casualties of more than 1.5 million people worldwide. The World Health Organizations (WHO) then declared a global health emergency. Consequently, the significant increase of cases had forced the Prime Minister of Malaysia to take a drastic measure by announcing a Movement Control Order (MCO) to all Malaysians. The MCO was a lifetime experience that shocked the whole nation when almost all government premises, schools, universities, and business enterprises had to be closed down within short notices. Among all, small and medium enterprises (SMEs) that represented more than 95% of the total business establishments were included. Currently, most of the sellers and buyers in Kelantan are involved in online business through several business groups in social media like Facebook. Some of the business groups include Niaga and Beli Online Kelantan, Info Perniagaan Rakyat Kelantan, Group Bisnes Online Terbesar di Kelantan, Kelantan Market Place and Iklan Niaga Kelantan. Despite the tremendous growth of online businesses nationwide, the performance of online businesses in Kelantan has yet to be explored. Therefore, this research aims to identify the effects of MCO experienced by online micro-enterprises in Kelantan. This study plans to investigate whether they also benefit from the overall growth in online business along with other online businesses nationwide. This study employed qualitative approach aiming at online microenterprises in Kelantan that operate using Facebook online business platform known as "Market Place". Microenterprises that trade in Market Place and originated from Kelantan will be identified for dissemination of online survey utilizing Google Form. It was identified that despite the stated increasing purchasing power enjoyed by large corporation, online microenterprises in Kelantan have experienced a reduction in their overall income. Limited financial resources, lack of knowledge as well as expertise have hindered these microenterprises to enjoy the benefits of doing online business